Narradores da exclusão ou a infância pobre na literatura brasileira contemporânea - Georgina Martins (Estudos de Literatura Brasileira Contemporânea)
This article’s intension is to investigate the literary representation of the ‘’poor childhood” in the contemporary Brazilian literature, as well as its alignment be- tween ethics and aesthetics for a literary construction of a model of childhood. Its purpose is also deepens the related questions, concerned to the subject, in order to show the differences and similarities amongst the various forms of narratives and the comprehension of such representation.The material for analysis are the short stories of Antonio Carlos Viana, Marcelino Freire and Rubens Figueiredo, whose texts reflect the situation of precariousness that we will find a significant part of the contemporary childhood